The Evolution of Party Policy and Cleavage Voting under Power-Sharing in Northern Ireland. Issue 2 (10th April 2021) - Tilley, James; Garry, John; Matthews, Neil
Abstract: This article argues that post-conflict consociational arrangements in ethnically divided societies incentivize moderation by political parties, but not policy differentiation outside the main conflict. This results in little policy-driven voting. Analysing party manifestos and voter survey data, we examine the evolution of party policy and cleavage voting under power-sharing in Northern Ireland 1998–2016. We find a reduction in ethno-national policy differences between parties and that ethno-nationalism has become less important in predicting vote choice for Protestants, but not Catholics. We also find little party differentiation in other policy areas and show that vote choices are largely independent of people's policy stances on economic or social issues. Our findings are thus largely consistent with a 'top-down' interpretation of political dynamics.